The Focal easy guide to Final cut pro X - Young, Rick, 1967- (Focal Press, 2014)
Master invaluable workflow tips that will allow you to tap into the full power of Final Cut Pro X and achieve results quickly, regardless of your skill level. Rick Young's Focal Easy Guide to Final Cut Pro X, Second Edition is the ultimate mentor for getting up and running with Apple's professional editing software. In this step-by-step, full-color guide, Young clearly explains the key concepts and vital knowledge you need to edit your project from start to finish, providing clear, time-saving instruction on producing and outputting using Final Cut Pro X. This new edition has been updated to include: A thorough introduction to Final Cut Pro X and the philosophy by which the software works Coverage of the complete postproduction process, including setup, importing, editing, audio, effects, and output Additional sections on Multicam Editing, working with Proxies, and effective media management of Libraries Instruction on encoding, distributing, and archiving your completed projects A companion website (www.focalpress.com/9781138785533) featuring downloadable video footage that you can edit using the techniques covered in the book Packed with tutorials and real-world examples, The Focal Easy Guide to Final Cut Pro X, Second Edition will take you through the ins and outs of the software and have you editing and outputting your movies in no time! Written for Final Cut Pro X version 10.1.3 and beyond.